Comparative Distortion Analysis of Welded T-Joint between 2D-Shell and 3D-Solid Element using FEA with Experimental Verification / Keval. P Prajadhiana...[et al.] - P Prajadhiana, Keval; Manurung, Yupiter HP; Zainir, Muhammad Zohdi; Yahya, Omar; Saedon, Juri; Shahriman, Mohd; Omar, Abdul Rahman; Kuntjoro, Wahyu; Kasim, Khairulnizam; Ishak, Dendi P.; Bauer, Alexander; Graf, Marcel (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
In this paper, three different finite element simulations of welded T-Joint are to be computed using 2D-shell and 3D-solid element types. The assigned element types are built and modelled on T-joint plate with thickness of 4 mm. The thermo-mechanical FEM simulation using MSC Marc/Mentat is implemented throughout the analysis. The angular distortion induced by welding process on the web is to be analysed under similar heat input and clamping condition on the stiffener. The selected heat source model is Goldak's double ellipsoid which is normally used for arc welding processes.In order to verify the simulation process, selected one-pass and double-sided GMAW process with fully automated experimental procedure was conducted using the exactly similar parameters assigned in FEM simulation. A measurement point analysis is furthercarried out to assess the displacement value of the actual T-Joint welding process by using Coordinate Measuring Machine (CMM) and to compare with the result of FEM simulation.It is found out that, for this kind of joint design and geometry, conducted FEM procedure shows good agreement on distortion tendency of the web within the range of percentage error up to 20%. However, the element types shell and solid without table do not indicate significant difference in simulation result compared to solid element with table.